Less refined ingredients have lower environmental impact – A life cycle assessment of protein-rich ingredients from oil- and starch-bearing crops. (10th April 2021) - Lie-Piang, Anouk; Braconi, Nicoló; Boom, Remko M.; van der Padt, Albert
Abstract: In the coming decades, meat-based protein foods will increasingly be replaced by plant-based protein foods. These are typically prepared from highly refined protein isolates or concentrates, which require a lot of energy and auxiliary chemicals to be produced. Milder techniques such as dry fractionation or mild aqueous fractionation deliver alternative ingredients that have a multicomponent character but do not need the same amount of chemicals and energy. This study aims to assess the effect of reducing the degree of refining on the environmental impact using a life cycle assessment. The functional unit was 1000 kg of the processed crop. As protein is considered key in these ingredients, the functional unit of 1 kg of protein in the produced fractions was also assessed. The contribution of processing to the overall impact was found to be significant and, in some cases, larger than the contribution by the crop cultivation. Therefore, any analysis of the environmental impact should include both. Reducing the degree of refining substantially reduces global warming potential, human carcinogenic toxicity, fossil resource scarcity, and water consumption. However, for all impact categories, drying remains the largest contributor. The global warming potential of less refined ingredients was still lower compared to the conventionally refined ingredients when expressed per kg of protein, despite the significantly lower amount of protein. The fractions obtained through mild aqueous fractionation have a higher protein yield and a lower global warming potential compared to conventional full refining. Both dry fractionation and the combination of dry and mild aqueous fractionation substantially lower the environmental impact, but the protein yield and purity are also considerably lower. Overall, linking environmental impact to protein purity and yield allows for a comprehensive selection of sustainable food ingredients. Highlights: A life cycle assessment was performed on different degrees of refined ingredients. The footprint of processing is equal or larger than cultivation of ingredients. Drying is mostly responsible for the impact of ingredient processing. Protein purity, yield, and footprint were linked to pick sustainable ingredients. Milder processes can deliver protein-rich ingredients with a lower footprint.